Naturally occurring anti-P1 with high thermal amplitude complicating ABO blood grouping - Shirin Ferdowsi; Saeed Mohammadi; Moharram Ahmadnezhad; Fahimeh Herfat; Azita Rezvani; Peyman Eshghi; Arezoo Oodi (Asian Journal of Transfusion Science)
Anti-P1 is immunoglobulin M type and occurs naturally; it is often detected as a weak- and cold-reactive antibody. However, in rare cases, it is reactive at 37°C or shows hemolytic transfusion reactions. The presence of high thermal amplitude of anti-P1 cannot be ignored and requires cross-match compatible red blood cells for transfusion. In the present study, we report three cases with ABO discrepancy due to anti-P1 that was identified as a cold-reacting antibody with high thermal amplitude.